Relationship Between CD4+ Cell with GenExpert Molecular Mycobacterium tuberculosis Test in HIV/AIDS patients - Al’fira Gita Islami; Rizana Fajrunni'mah; Mega Mirawati (UrbanGreen, 2022)
CD4+ cells in HIV/AIDS patients is an examination that serves to monitor the regulation of the immune system. HIV/AIDS patients experience a decrease in the number of CD4+ cells which results in various opportunistic infections, one of which is caused by Mycobacterium tuberculosis. This study aims to determine the relationship between the results of CD4+ cell with GenExpert Molecular Mycobacterium tuberculosis Test. This study was based on an analytic observational cross-sectional design on 53 samples of HIV/AIDS patients at Budhi Asih Hospital. Data analyze using Fisher Exact statistical test with α = 0.05. The result showed percentage CD4+ cells <200 with positive TCM result 48 (86,4%). CD4+ cells >200 with GenExpert positif result 0 (0,0%). The results showed that there was no relationship between CD4+ cell examination and TCM GenExpert MTB examination in HIV/AIDS patients (p = 0.574). From the result we can conclude that maybe other infection has happened.